Telomere dysfunction is associated with dark‐induced bleaching in the reef coral Stylophora pistillata. Issue 23 (15th October 2021) - Rouan, Alice; Pousse, Mélanie; Tambutté, Eric; Djerbi, Nadir; Zozaya, William; Capasso, Laura; Zoccola, Didier; Tambutté, Sylvie; Gilson, Eric
Abstract: Telomere DNA length is a complex trait controlled by both multiple loci and environmental factors. A growing number of studies are focusing on the impact of stress and stress accumulation on telomere length and the link with survival and fitness in ecological contexts. Here, we investigated the telomere changes occurring in a symbiotic coral, Stylophora pistillata, that has experienced continuous darkness over 6 months. This stress condition led to the loss of its symbionts in a similar manner to that observed during large‐scale bleaching events due to climate changes and anthropogenic activities, threatening reef ecosystems worldwide. We found that continuous darkness was associated with telomere length shortening. This result, together with a phylogenetic analysis of the telomere coral proteins and a transcriptome survey of the continuous darkness condition, paves the way for future studies on the role of telomeres in the coral stress response and the importance of environmentally induced telomere shortening in endangered coral species.